Analgesic effect of tramadol in the rat - Dhasmana K M; Banerjee A K; Rating W; Erdmann W (Acta Pharmacologica Sinica, 2016)
The analgesic effect of tramadol was studied in the rat using tail flick and hot plate tests following intrathecal and subcutaneous administrations. Tramadol had only a short-lasting analgesic effect (20 min) on intrathecal administration which may be due to rapid removal from the subarachnoid space. Its analgesic effects were antagonized by pretreatment with naloxone. It seems that the opiate system may involve in the analgesic effect of tramadol, while the noradrenergic, serotonergic and cholinergic systems may play a modulating role.